Investment possibilities in the Eastern Region of the Federation of Nigeria - Eastern Nigeria (Nigeria). Legislature. House of Assembly (Enugu: Government Printer, Eastern Region, 1960)
The booklet is aimed at providing prospective investors and entrepreneurs, particularly those from abroad who require basic facts and information about the people, natural resources and investment opportunities in Eastern Nigeria.
Government publication, State or province government publication
rpm 03/05/2017
Loans
Keywords: Investments, Foreign -- Nigeria; Nigeria -- Economic conditions; Economic history; Investments, Foreign; Enugu -- Nigeria